2021
DOI: 10.1039/d1an00436k
|View full text |Cite
|
Sign up to set email alerts
|

An electrochemical biosensor for simultaneous detection of breast cancer clinically related microRNAs based on a gold nanoparticles/graphene quantum dots/graphene oxide film

Abstract: An electrochemical biosensor employing a gold nanoparticles/graphene quantum dots/graphene oxide composite modified electrode is developed for the multiplex detection of miRNA breast cancer biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(36 citation statements)
references
References 65 publications
0
36
0
Order By: Relevance
“…[31] developed a 12‐miRNA panel, which yielded an AUC of 0.94, a sensitivity of 0.84, a specificity of 0.91, a PPV of 0.90, and an NPV of 0.85, in 216 patients with breast cancer and 214 normal controls. Several other lncRNAs (AUC 0.74–0.95) [32–34], microRNA (AUC 0.86–0.99) [35–37], and DNA methylation panels (AUC 0.58–0.98) [38] also showed high diagnostic accuracy, which is corresponded to the accuracy of serum SEMA4C levels in diagnosing breast cancer. However, these tests are not always readily available and lack clinical application in low‐resource settings.…”
Section: Discussionmentioning
confidence: 99%
“…[31] developed a 12‐miRNA panel, which yielded an AUC of 0.94, a sensitivity of 0.84, a specificity of 0.91, a PPV of 0.90, and an NPV of 0.85, in 216 patients with breast cancer and 214 normal controls. Several other lncRNAs (AUC 0.74–0.95) [32–34], microRNA (AUC 0.86–0.99) [35–37], and DNA methylation panels (AUC 0.58–0.98) [38] also showed high diagnostic accuracy, which is corresponded to the accuracy of serum SEMA4C levels in diagnosing breast cancer. However, these tests are not always readily available and lack clinical application in low‐resource settings.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the assaying of multiple miRNA markers from one sample is necessary for accurate detection and higher specificity. 45 Only handful of research has been reported thus far on the multiplexed and simultaneous detection of only two or three miRNAs using biosensors for early BC detection [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] from the body fluids. To the best of our knowledge, there is no systematic review conducted on the electrochemical biosensors for multiplexed DCIS miRNAs detection.…”
Section: Dcis Stages Grades and Incidencementioning
confidence: 99%
“…The developed biosensor reveals simultaneous sensing with sensitivity values of 3.5, 2.9 and 1.8 μA/pM for the three miRNAs and also demonstrated selective recovery from human serum samples. 48 The significance of the design of the reported biosensor is that it is simple and without any labelling molecules, less time for the fabrication and detection, low cost, and reduced assay procedure.…”
Section: Ecs Sensors Plus 2022 1 021602mentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, investigations have also been conducted using probes anchored by different redox species in CD-based electrochemical sensors for the simultaneous sensing of multiple nucleic acid biomarkers. A recent study by Pothipor et al revealed that the designed three-screen-printed carbon electrode (3SPCE) array sensor based on the modification of gold nanoparticles (AuNPs)/GQDs/GO was able to detect miRNA-21, miRNA-155, and miRNA-210 biomarkers [ 78 ]. The dysregulation of miRNAs has been linked to the etiology of breast cancer, and studies have demonstrated that miRNAs expression profiles may be associated with tumor aggressiveness, treatment response, and patient prognosis in breast cancer [ 79 ].…”
Section: Biosensing Technologymentioning
confidence: 99%